Discovery of novel 2′, 4′-dimethyl-[4, 5′-bithiazol]-2-yl amino derivatives as orally bioavailable TRPV4 antagonists for the treatment of pain: Part 2. Issue 20 (15th October 2016) - Tsuno, Naoki; Yukimasa, Akira; Yoshida, Osamu; Suzuki, Shinji; Nakai, Hiromi; Ogawa, Tomoyuki; Fujiu, Motohiro; Takaya, Kenji; Nozu, Azusa; Yamaguchi, Hiroki; Matsuda, Hidetoshi; Funaki, Satoko; et al.
Graphical abstract: Abstract: A series of 2′, 4′-dimethyl-[4, 5′-bithiazol]-2-yl amino derivatives have been identified as selective TRPV4 antagonists that display inhibition potencies against 4α-phorbol 12, 13-didecanoate (4αPDD), well known as a TRPV4 selective agonist and/or a hypotonicity. In particular, 9-(6-((2′, 4′-dimethyl-[4, 5′-bithiazol]-2-yl)amino)nicotinoyl)-3-oxa-9-azabicyclo[3.3.1]nonan-7-one showed an analgesic effect in Freund's Complete Adjuvant (FCA) induced mechanical hyperalgesia model in guinea pig (reported in Part 1). However, there are some concerns such as species differences and the need for higher plasma exposure to achieve target efficacy for evaluation by an in vivo pain model. In this Letter, we report the resolution of some of the problems by further optimizing the chemical scaffold.